STRATIGRAPHIC ANALYSIS AND DISTRIBUTION OF ROCK UNITS IN THE CIPATAT AREA, WEST BANDUNG REGENCY, WEST JAVA PROVINCE, INDONESIA - Margereta, Natasya; Haryanto, Iyan; Abdurrokhim, Abdurrokhim (Universitas Padjadjaran, 2026)
Geological mapping of the Cipatat area, West Bandung Regency, West Java Province was conducted at a scale of 1:12,500 to establish the stratigraphic succession, spatial distribution of rock units, and structural configuration of the region. Three rock units were identified spanning the Late Oligocene to Quaternary: the Rajamandala Limestone Unit (TOMBG), the Citarum Sandstone Unit (TMBP), and the Quaternary Volcanic Unit (QV). The Rajamandala Limestone, deposited in a shallow neritic carbonate platform, is biostratigraphically constrained to zones Te3–Tf1 based on larger foraminifera including Lepidocyclina, Operculina, Miogypsina, and Cycloclypeus, while petrographic analysis confirms mudstone to packstone facies. The overlying Citarum Sandstone Unit represents a deep-marine turbidite system characterized by graded bedding, parallel lamination, and load casts defining a Bouma sequence dominated by the Tb facies, with foraminifera assemblages assigning deposition to Middle Miocene zones N5–N9 and reflecting progressive basin deepening from neritic to bathyal conditions. Petrographic analysis of the sandstone further supports classification as volcanic-derived lithic wacke, consistent with a volcanogenic provenance. The Quaternary Volcanic Unit unconformably caps the sequence, marking a shift from marine sedimentation to subaerial volcanism. Structural analysis reveals three major fault systems — the Cibuntu, Cibrengkok, and Cilimus River Faults — developed under a northwest–southeast compressional regime attributed to Miocene–Plio-Pleistocene Sunda Arc convergence, generating west–east-trending fold pairs that govern the present ridge-valley morphology and lithological distribution across the study area